(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
The relevance of this topic lies in the development of communicative competence of students. Students are a typical group of future personnel who must have a special sense of responsibility for their future profession. Interactive methods contribute to the active interaction of students. They teach how to express their thoughts, argue their position and adapt to various communicative situations. If he does not have communication skills, then he will not be able to enter into communication and will not know a complete and broad understanding of the information. The reason for such high attention to interactive methods is the need for modern training not only professional, but also communicative competence.